Coaching and talent development in esports: a theoretical framework and suggestions for future research - Bubna, Kabir; Trotter, Michael Geoffrey; Watson, Matthew; Polman, Remco (Frontiers in Psychology, 2023)
Esports is a growing phenomenon that is capturing the attention of individuals worldwide, and has grown to provide professional and lucrative careers for those who reach the upper echelons. One question that arises, is how esports athletes develop the necessary skills required to improve and compete. This perspective piece opens the door to skill acquisition within esports and how research through an ecological approach can benefit researchers and practitioners as they understand the various perception-action couplings and decision-making challenges faced by esports athletes. We will identify and discuss what constraints look like in esports, the role of affordances, and theorise the implementation of a constraints-led approach in contrasting esports genres. As esports is technology-heavy in nature and generally sedentary, the use of eye-tracking technology is argued to represent an effective method to better understand perceptual attunement between individuals and teams. Future research into skill acquisition in esports is needed to develop a clearer picture of what makes the greatest esports player so great, and how newer players can be developed effectively.